1992
DOI: 10.1128/jvi.66.6.3415-3423.1992
|View full text |Cite
|
Sign up to set email alerts
|

Two amino acid substitutions within the capsid are coordinately required for acquisition of fibrotropism by the lymphotropic strain of minute virus of mice

Abstract: Nucleotide changes at both codons 317 and 321 in the VP2 capsid gene of the immunosuppressive strain of the murine parvovirus minute virus of mice, MVM(i), are required to create a virus capable of growing in A9 fibroblasts. This double mutant virus, ILB1, has growth characteristics very similar to those of the prototype fibrotropic strain MVM(p) in both single-and multiple-round infections of fibroblasts and is about 100-fold better at infecting fibroblasts than MVM(i). When only one nucleotide position is ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 33 publications
5
44
0
Order By: Relevance
“…This similarity in glycan profile thus fails to explain the differences in tropism for these cells between these MVM viruses based on differential cell surface glycan receptor recognition. These observations support previous claims that the determinant of differential cell and tissue tropism for MVMp and MVMi is post cell entry [26,28,36,58,59]. These previous reports identified amino acids at and surrounding the depression at icosahedral 2-fold axes of the capsid, which differ between the viruses, as playing a crucial role in dictating these differences.…”
Section: Cellular Glycan Profiling Parallels Glycan Array Screening Datasupporting
confidence: 89%
“…This similarity in glycan profile thus fails to explain the differences in tropism for these cells between these MVM viruses based on differential cell surface glycan receptor recognition. These observations support previous claims that the determinant of differential cell and tissue tropism for MVMp and MVMi is post cell entry [26,28,36,58,59]. These previous reports identified amino acids at and surrounding the depression at icosahedral 2-fold axes of the capsid, which differ between the viruses, as playing a crucial role in dictating these differences.…”
Section: Cellular Glycan Profiling Parallels Glycan Array Screening Datasupporting
confidence: 89%
“…Although the alignment with the CPV sequence is not as good as for surface loops 1 and 2, CPV surface loop 4 aligns roughly between residues 440 and 500 (19,29), thus potentially encompassing several of these changes. Furthermore, the host range determinants in the FPV (1,69) and minute virus of mice (13,14,35) systems govern the surface topography of the viral particle on a spike near the threefold axis symmetry formed by the interdigitation of surface loops 3 and 4 in a complex fashion (29,70). Our previous chimeras (19) did not include any in which VP2 residues 359 to 647 from a pathogenic strain were included in an ADV-G background in the absence of the residue 50 to 226 host range determinant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the determinants have been localized to specific sites on the viral particle (1,29,69,70). In addition, the pathogenicity and host range of strains of minute virus of mice are also governed by capsid protein sequences (13,14,35).…”
mentioning
confidence: 99%
“…Previous studies reported successful targeting and oncolysis of human tumor cell lines (29,49,66). The two strains included in our study, the fibrotropic prototype MVMp and the immunosuppressive strain MVMi, differ in their capsid protein, which is critical for differences in cell targeting and outcome of infection (7,55).…”
mentioning
confidence: 95%